2001
DOI: 10.1111/j.1572-0241.2001.05334.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of health care in inflammatory bowel disease: development of a reliable questionnaire (QUOTE-IBD) and first results

Abstract: A short, valid, reliable questionnaire was developed to measure the opinions of patients with inflammatory bowel disease on quality of health care. The QUOTE-IBD can be used for identification of areas for improvement, with the aim of optimizing health care in inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Also surgery, younger age and longer disease duration play an important role in the experience of the quality of care (van der Eijk et al . , Pallis et al . , Masachs et al .…”
Section: Introductionmentioning
confidence: 99%
“…Also surgery, younger age and longer disease duration play an important role in the experience of the quality of care (van der Eijk et al . , Pallis et al . , Masachs et al .…”
Section: Introductionmentioning
confidence: 99%
“…Met name een multidisciplinaire aanpak, waarbij medische en nietmedische expertises verder op elkaar worden afgestemd, en de empirische evaluatie daarvan vormen een belangrijke uitdaging voor de toekomst. Recent ontwikkelde meetinstrumenten, de QUOTE-IBD, een-kwaliteit-vanzorg-maat, en de SIBDQ, een ziektespecifieke vragenlijst om de kwaliteit van leven te meten bij IBD-patie¨nten, komen hierbij van pas (Van der Eijk et al, 2001;Irvine et al, 1996). Relevante en actuele thema's die daarbij verdere verdieping verdienen zijn onder meer: communicatie, non-adherentie, vermoeidheid en stoppen met roken.…”
Section: Besluitunclassified
“… 16 These domains strongly align with NHS England, National Clinical Guidelines Centre (NICE) and Institute of Medicine (IOM) definitions of quality in health care, which advocate that care should be patient‐centric, safe, effective, efficient and equitable. 17 , 18 A scoping review identified a range of IBD‐specific instruments that measure experience‐related concepts, such as patient satisfaction, 6 patient knowledge, 19 patient concerns, 20 self‐efficacy 21 and quality of care, 22 but no validated PREM. To fill this knowledge gap, this study aimed to develop a PREM for people with IBDs to support IBD service evaluation.…”
Section: Introductionmentioning
confidence: 99%